Α″ Martensitic Twinning in Alpha + Beta Ti-3.5Al-4.5Mo Titanium Alloy. (19th May 2011) - Li, Changfu; Li, Geping; Yang, Yi; Varlioglu, Mesut; Yang, Ke
Abstract : The twinning structure of the orthorhombicα ′ ′ martensite phase in alpha + beta Ti-3.5Al-4.5Mo (wt%) titanium alloy was studied using X-ray diffraction and transmission electron microscopy by water quenching from below transus temperatures. While water quenching from 910 ∘ C induced the formation of{ 110 } ∘ twins, quenching from 840 ∘ C formed theα ′ ′ martensite with{ 111 } ∘ type I twins. The effect of the principle strains on the twinning structure was discussed. As compared to the previous studies, the principle strains play an important role in the formation of the twinning type.